Bioactive Peptides against Human Apicomplexan Parasites - Norma Rivera-Fernández; Jhony Anacleto-Santos; Brenda Casarrubias-Tabarez; Teresa de Jesús López-Pérez; Marcela Rojas-Lemus; Nelly López-Valdez; Teresa I. Fortoul (MDPI AG, 2022)
Apicomplexan parasites are the causal agents of different medically important diseases, such as toxoplasmosis, cryptosporidiosis, and malaria. Toxoplasmosis is considered a neglected parasitosis, even though it can cause severe cerebral complications and death in immunocompromised patients, including children and pregnant women. Drugs against Toxoplasma gondii, the etiological agent of toxoplasmosis, are highly toxic and lack efficacy in eradicating tissue cysts, promoting the establishment of latent infection and acute relapsing disease. Cryptosporidiosis has been recognized as the most frequent waterborne parasitosis in US outbreaks; anti-cryptosporidium drug discovery still faces a major obstacle: drugs that can act on the epicellular parasite. Severe malaria is most commonly caused by the progression of infection with Plasmodium falciparum. In recent years, great progress has been made in the field of antimalarial drugs and vaccines, although the resistance of P. falciparum to artemisinin has recently gained a foothold in Africa. As seen, the search for new drugs against these parasites remains a challenge. Peptide-based drugs seem to be attractive alternative therapeutic agents recently recognized by the pharmaceutical industry, as they can kill different infectious agents and modulate the immune response. A review of the experimental effects of bioactive peptides on these parasites follows, along with comments. In addition, some biological and metabolomic generalities of the parasites are reviewed to elucidate peptide mechanisms of action on Apicomplexan targets.